Processing punctuation and word changes in different editions of prose fiction - Carrol, Gareth; Conklin, Kathy; Guy, Josephine; Scott, Rebekah (John Benjamins, 2015)
The digital era has brought with it a shift in the field of literary editing in terms of the amount and kind of textual variation that can reasonably be annotated by editors. However, questions remain about how far readers engage with textual variants, especially minor ones such as small-scale changes to punctuation. In this study we present an eye-tracking experiment investigating reader sensitivity to variations in surface textual features of prose fiction. We monitored eye movements while participants read textual variants from Dickens and James, hypothesising that readers may pay more attention to lexical rather than punctuation changes. We found longer reading times for both types, but only lexical changes also increased reading times for the rest of the sentence. In addition, eye movement behaviour and conscious ability to report changes were highly correlated. We discuss the implications for how such methods might be applied to questions of “literary” significance and textual processing.